Energy efficiency optimization for sub-connected active reconfigurable intelligent surface-assisted wideband cell-free networks - Gangcan SUN; Shuo WANG; Bing NING; Wanming HAO (Tongxin xuebao)
In the face of the high power consumption issue caused by the dense deployment of base stations in cell-free networks, a wideband cell-free network system with sub-connected active reconfigurable intelligent surface (RIS) was proposed.Firstly, based on the constraints of maximum power consumption at the active RIS, amplification factor, and maximum power consumption at the base station, a joint precoding design problem for the base station and RIS was formulated to maximize the energy efficiency.To solve the non-convex problem, advanced techniques including alternating optimization, block coordinate descent, Lagrange dual reconstruction, and multidimensional complex quadratic transformation were applied to transform the original problem into multiple sub-problems.By iteratively solving each sub-problem, the solutions of the original problem was ultimately obtained.The simulation results validate the effectiveness of the proposed scheme.